1997
DOI: 10.1099/0022-1317-78-11-2761
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a defective hepatitis C virus genome from the ascitic fluid of a patient with hepatocellular carcinoma.

Abstract: A defective hepatitis C virus (HCV) genome in the ascitic fluid of a patient with hepatocellular carcinoma was cloned and sequenced up to the 3h poly(U) stretch. When compared with the published Taiwanese HCV sequence, this defective genome contained deletions of single nucleotides at eight sites, double nucleotides at two sites, triple nucleotides at four sites, quadruple nucleotides at one site and replacement of a short stretch of sequence at one site. For comparison, the corresponding regions containing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…At the moment, we have no information about the molecular events that might lead to the initiation of ARFP synthesis; however, several possibilities can be considered+ For example, the AUG of the main ORF, or an up-stream AUG, could be the start site of translation, with the reading frame slipping forward to bypass the stop codon at bases 2-4 (in the ϩ1 reading frame)+ Frame shifts are known to occur during gene expression of many viruses (Brierley, 1995)+ Alternatively, translation of ARFP might involve a non-AUG initiator codon; in fact, the HCV IRES has the power to direct translation from codons other than AUG (Reynolds et al+, 1995)+ Moreover, a recent report indicates that a novel translation initiation mechanism can lead to the synthesis of out-of-frame peptides (even some without upstream AUG initiation codons), which are then expressed by MHC class I molecules and stimulate immune responses (Malarkannan et al+, 1999)+ This report describes a series of non-AUG codons that allow translation of out-of-frame peptides at levels that elicit robust T cell responses+ One of these unusual start codons is AUC+ This unusual start codon is the third in-frame codon in .90% of the ϩ1 alternate reading frames of the reported HCV sequences+ If this were the start codon for the ARFP, then the expected product would range from 122 to 158 amino acids in the majority of sequences+ Finally, RNA stuttering could modify the sequence of HCV RNA during RNA replication, generating a new RNA that has ARFP as its translation product+ Stuttering gives rise to the RNA sequences required for the expression of proteins in most members of the Paramyxoviridae family (Liston & Briedis, 1995)+ If stuttering occurs during HCV replication, it could lead to the expression of chimeric proteins with amino terminal portions of the HCV core protein linked to carboxy-terminal portions of ARFP+ HCV sequences that could give rise to such chimeric proteins have been detected in PCR products from hepatocellular carcinoma (Ruster et al+, 1996) and the ascitic fluid of a patient with hepatocellular carcinoma (Yeh et al+, 1997)+ Our studies do not indicate whether ARFP plays a role in the HCV life cycle, or is synthesized "fortuitously+" However, the ORF is present in all reported HCV genotypes, and all the infectious clones described to date+ If ARFP has an impact on cellular or viral function, its highly basic nature and lack of a known nuclear localization signal suggests an interaction with cytoplasmic RNA, perhaps HCV RNA itself+ A possible role of ARFP in cellular transformation must be considered in light of studies showing chimeric proteins containing portions of ARFP might be expressed in HCC tissue and ascitic fluid (Ruster et al+, 1996; Yeh et al+, 1997)+ ,0+025 a HCV (13/100) vs+ total non-HCV (3/104)…”
Section: Arfp Properties and Synthesismentioning
confidence: 99%
“…At the moment, we have no information about the molecular events that might lead to the initiation of ARFP synthesis; however, several possibilities can be considered+ For example, the AUG of the main ORF, or an up-stream AUG, could be the start site of translation, with the reading frame slipping forward to bypass the stop codon at bases 2-4 (in the ϩ1 reading frame)+ Frame shifts are known to occur during gene expression of many viruses (Brierley, 1995)+ Alternatively, translation of ARFP might involve a non-AUG initiator codon; in fact, the HCV IRES has the power to direct translation from codons other than AUG (Reynolds et al+, 1995)+ Moreover, a recent report indicates that a novel translation initiation mechanism can lead to the synthesis of out-of-frame peptides (even some without upstream AUG initiation codons), which are then expressed by MHC class I molecules and stimulate immune responses (Malarkannan et al+, 1999)+ This report describes a series of non-AUG codons that allow translation of out-of-frame peptides at levels that elicit robust T cell responses+ One of these unusual start codons is AUC+ This unusual start codon is the third in-frame codon in .90% of the ϩ1 alternate reading frames of the reported HCV sequences+ If this were the start codon for the ARFP, then the expected product would range from 122 to 158 amino acids in the majority of sequences+ Finally, RNA stuttering could modify the sequence of HCV RNA during RNA replication, generating a new RNA that has ARFP as its translation product+ Stuttering gives rise to the RNA sequences required for the expression of proteins in most members of the Paramyxoviridae family (Liston & Briedis, 1995)+ If stuttering occurs during HCV replication, it could lead to the expression of chimeric proteins with amino terminal portions of the HCV core protein linked to carboxy-terminal portions of ARFP+ HCV sequences that could give rise to such chimeric proteins have been detected in PCR products from hepatocellular carcinoma (Ruster et al+, 1996) and the ascitic fluid of a patient with hepatocellular carcinoma (Yeh et al+, 1997)+ Our studies do not indicate whether ARFP plays a role in the HCV life cycle, or is synthesized "fortuitously+" However, the ORF is present in all reported HCV genotypes, and all the infectious clones described to date+ If ARFP has an impact on cellular or viral function, its highly basic nature and lack of a known nuclear localization signal suggests an interaction with cytoplasmic RNA, perhaps HCV RNA itself+ A possible role of ARFP in cellular transformation must be considered in light of studies showing chimeric proteins containing portions of ARFP might be expressed in HCC tissue and ascitic fluid (Ruster et al+, 1996; Yeh et al+, 1997)+ ,0+025 a HCV (13/100) vs+ total non-HCV (3/104)…”
Section: Arfp Properties and Synthesismentioning
confidence: 99%
“…In addition, phylogenetic analysis with the core11 amino-acid sequence has shown that the core11 variants obtained from HCC samples differ from those in nontumor cells, consistent with the selection of core11 variants with modified functional properties in HCV-induced HCC. Previous studies also reported the accumulation of characteristic mutations in specific regions of the HCV core/core11 RNA sequence in patients with HCC, these mutations being associated with an increase in the production of alternative forms of core/core11 proteins in cell-free systems in several cases (46)(47)(48)(49)(50)(51).…”
Section: Evidence For Core11 Protein Production During Natural Hcv Inmentioning
confidence: 99%
“…These studies suggest a link between coreϩ1/ARFP and development of liver cancer (22)(23)(24)(25)(26)(27). Conversely, coreϩ1/ARFP has no obvious effect on virus replication following electroporation of Huh7-Lunet cells with fulllength JFH1 wild-type and mutated viral RNAs or in mice xenografted with human liver tissue (28).…”
mentioning
confidence: 99%